Análises morfológica e histoquímicas do ventrículo e do cérebro de operárias recém emergidas de Apis Mellifera L. (Hymenoptera, Apidae) tratadas com Thiamethoxam - Oliveira, Regiane Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Apis mellifera honeybees are social insects of economic importance, by providing honeybee products, and by the pollination of natural areas of vegetation or agricultural areas. The constant use of pesticides, including the thiamethoxam, which is an insecticide belonging to the class of neonicotinoids with neurotoxic action, is subjecting pollinators to situations of severe stress, which has been evidenced by the decrease in the density of honeybees in many parts of the world. By these considerations, the present study aimed to assess the acute toxicity of thiamethoxam for newly emerged workers of A. mellifera, and to investigate the effect of sublethal doses of this insecticide on the survival time and its cytotoxicity to the brain and midgut to the honeybees. It was established the value of the lethal concentration 50 (LC50) equal to 4.28 ng thiamethoxam/μL of food and from it, the sublethal concentrations of 0.428 ng thiamethoxam/μL (CL50/10) and 0.0428 ng thiamethoxam/μL (CL50/100), which were used in bioassays of intoxication of the honeybees. After the bioassays the bees were dissected and the brain and midguts were collected to analyze possible morphological (staining with Hematoxylin-Eosin) and histochemical alterations (Xylidine Ponceau technique, and Feulgen and PAS reactions) caused by exposure to thiamethoxam, and to calculate the lethal time (LT50) for the workers. The duration of the bioassays was 8 days after beginning of feeding. The results obtained showed that the thiamethoxam is toxic to newly-emerged workers of A. mellifera, causing changes in survival time of individuals. This study also shown that the thiamethoxam causes morphological and histochemical alterations on the midgut and brain of workers. These alterations may be reflected in physiological and behavioral changes that can modify the operation of the colony

As abelhas Apis mellifera são insetos sociais de grande importância econômica, seja ela direta, através do fornecimento de produtos apícolas, ou indireta, pela polinização de áreas de vegetação natural ou de áreas agrícolas. O uso constante de agrotóxicos, dentre eles o thiamethoxam, que é um inseticida pertencente á classe dos neonicotinoides, com ação neurotóxica, vem submetendo os polinizadores a situações de estresse severo, o que tem sido evidenciado pela queda na densidade das abelhas em várias partes do mundo. Diante destas considerações, o presente trabalho teve por objetivos avaliar a toxicidade aguda do thiamethoxam para operárias recém emergidas A. mellifera, bem como investigar o efeito de dose subletal deste inseticida sobre o tempo de sobrevivência e sua citotoxicidade para o cérebro e intestino destas abelhas. Estabeleceu-se o valor da concentração letal 50 (CL50) igual a 4,28 ng de thiamethoxam/μL de alimento e, a partir dela, as concentrações subletais deste inseticida, sendo elas, de 0,428 ng de thiamethoxam/μL (CL50/10) e de 0,0428 ng de thiamethoxam/μL (CL50/100), que foram utilizadas em bioensaios de intoxicação das abelhas, que visaram a coleta de cérebros e ventrículos para análise de possíveis alterações morfológicas (coloração com Hematoxilina-Eosina) e histoquímicas (técnica de Xylidine Ponceau e reações de Feulgen e PAS) causadas pela exposição ao thiamethoxam, e para o cálculo do tempo letal (TL50) para as operárias. A duração dos experimentos foi de 8 dias após o início do fornecimento do alimento. Pôde-se concluir que o thiamethoxam é tóxico para operárias recém emergidas, causando, além de alterações morfológicas e histoquímicas nos órgãos analisados, alteração no tempo de sobrevivência dos indivíduos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Abelha; Morfologia (Animais); Histoquimica; Coração - Ventriculos; Cérebro; Toxicologia